Doctor on a mountaineering expedition. - A'Court, C; Stables, R; Travis, S (1995)
Doctors are welcome members on mountaineering expeditions to remote areas, but practical advice on how to prepare and what kit to take can be difficult to find. This article is a ragbag of useful advice on diverse topics. It explains the necessary preparation, provides tips for a healthy expedition, and summarises the common disorders encountered at high altitude. The comprehensive drug and equipment lists and first aid kit for climbers were used for the 1992 Everest in winter expedition. They are there to be sacrificed to personal preference and the experience and size of individual expeditions.